Community-Based Policing Strategies for Promoting Development and Stability in Kogi State - Miller, Dantawaye Gajere (African Journal of Stability and Development (AJSD), 2025)
Kogi State, like many regions in Nigeria, grapples with persistent insecurity, community mistrust, and underdevelopment. Armed robbery, kidnapping, communal clashes, and political violence continue to undermine grassroots peace efforts and economic progress. In response to these challenges, community-based policing has emerged as an alternative approach aimed at improving security outcomes by fostering collaboration between law enforcement and local stakeholders. This study explores the role of community policing in promoting development and stability across selected communities in Kogi State. Adopting a qualitative research design, the study utilised data from key informant interviews, focus group discussions, and official reports from community policing units and civil society organisations. The analysis focused on local perspectives, policing strategies, and collaborative frameworks involving vigilantes, neighbourhood watch groups, and traditional authorities. Findings reveal that effective community policing has led to increased public trust in security agencies, improved information flow, and more proactive responses to crime. The involvement of local actors, particularly through neighbourhood security groups and multi-stakeholder dialogue platforms, has enhanced social cohesion and contributed to a decline in petty crimes and communal disputes. However, persistent challenges such as inadequate funding, poor training, and political interference continue to limit the impact. The study concludes that community-based policing, when properly structured and supported, can significantly contribute to grassroots stability, promote participatory governance, and foster long-term local development. It recommends strengthening institutional frameworks, enhancing community-police relations, and ensuring inclusive security planning at the local government level.